2016
DOI: 10.18632/oncotarget.10299
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in regulatory regions of microRNAs are associated with lung cancer risk

Abstract: Genetic variants in regulatory regions of some miRNAs might be associated with lung cancer risk and survival. We performed a case-control study including 1341 non-small cell lung cancer (NSCLC) cases and 1982 controls to evaluate the associations of 7 potentially functional polymorphisms in several differently expressed miRNAs with NSCLC risk. Each SNP was also tested for the association with overall survival of 1001 NSCLC patients. We identified that rs9660710 in miR-200b/200a/429 cluster and rs763354 in miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…A study on NSCLC tissues using miRNA microarray demonstrated that miR-30a was downregulated in both adenocarcinomas (14/20) and squamous cell carcinomas (20/20) (P=0.448) (13). Other studies (14) arrived to the same conclusion and revealed that its low expression was associated with cancer risk and indicated poor prognosis (15). In vitro experiment (16) also suggested miR-30a was downregulated in NSCLC A549 cells compared with BEAS-2B normal lung epithelial cells, overexpression of miR-30a could inhibit A549 lung cancer cell malignancy (6,16).…”
Section: Introductionmentioning
confidence: 59%
“…Functional studies also revealed miR-30a-3p could act as a tumor suppressor in hepatocellular carcinoma (Wang et al, 2014), clear cell renal cell carcinomas (Mathew et al, 2014) and gastric cancer . Very recently, several studies highlighted the role of miR-30a-3p in lung cancer, and demonstrated that miR-30a-3p was significantly decreased in lung cancer and that miR-30a-3p down-regulation played important roles in the metastatic progression of lung cancer (Daugaard et al, 2017;Xie et al, 2016;Zhang et al, 2017). More importantly, tumor-derived exosomal miR-30a-3p was specifically down-regulated in NSCLC patients and could serve as diagnostic biomarkers for early-stage NSCLC (Jin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%